Association between left atrial enlargement and obstructive sleep apnea in a general population of 71‐year‐old men. (24th August 2017) - Holtstrand Hjälm, Henrik; Fu, Michael; Hansson, Per‐Olof; Zhong, You; Caidahl, Kenneth; Mandalenakis, Zacharias; Morales, David; Ergatoudes, Constantinos; Rosengren, Annika; Grote, Ludger; Thunström, Erik
Summary: Left atrial enlargement has been shown to be associated with obstructive sleep apnea in patients with coronary artery disease and in sleep clinic cohorts. However, data from the general population are limited. The aim of this study was to investigate whether there is an association between obstructive sleep apnea and left atrial enlargement in a random sample from a general population of 71‐year‐old men. As part of the longitudinal population study The Study of Men Born in 1943, we analysed cross‐sectional data for 411 men, all 71 years old, who had participated in an overnight home sleep study and a standardized echocardiographic examination. Of the 411 men, 29.4% had moderate to severe obstructive sleep apnea [apnea–hypopnea index score of ≥15 ( n = 121)]. These participants showed a significantly higher frequency of systolic heart failure, hypertension, overweight, had greater waist circumference as well as higher left atrial areas compared with men with no or mild obstructive sleep apnea (23.7 ± 5.5 cm 2 versus 21.6 ± 4.5 cm 2, P < 0.001). In a linear regression analysis, obstructive sleep apnea was significantly associated with left atrial enlargement after adjusting for overweight, atrial fibrillation, heart failure with reduced ejection fraction, hypertension and mitral regurgitation. Compared with individuals without obstructive sleep apnea, the mean left atrial area was 1.7 ± 1.5 cm 2 larger in men with severe obstructive sleep apnea ( P < 0.05) and 1.3 ± 1.1 cm 2 larger among men with moderate obstructive sleep apnea ( P < 0.05). In this cross‐sectional study of 71‐year‐old men from the general population, left atrial area was independently associated with prevalence and severity of obstructive sleep apnea.